Study on the effect of habitat function change on waterbird diversity and guilds in Yancheng coastal wetlands based on structure–function coupling - Cheng Wang (Elsevier, 2021)
In recent years, due to human activities and global climate change, the number and area of waterbird habitats in Yancheng coastal wetlands, a newly established world natural heritage site, have been shrinking, the function of the waterbird habitats has been degraded to varying degrees, and the safety of waterbird populations and habitats has been threatened. Therefore, in this study, waterbird habitat functions at the regional scale were assessed by using spatial principal component analysis (SPCA). According to the load matrix of principal components and the Redundancy analysis (RDA) method, the driving force of habitat function change and the mechanisms of their effects on waterbird guilds and diversity were revealed. The results showed that the areas of the highest and high habitat function grades continued to decline from 1987 to 2019, and the areas of the lowest and low grades of habitat function continued to increase. The overall habitat functions in the waterbird distribution areas were high, but the functional grades within different habitat sites were obviously decreasing. The main driving factors affecting habitat function change in Yancheng coastal wetlands from 1987 to 2019 were habitat types, habitat area, habitat diversity, habitat fragmentation, number of residential areas and reclamation intensity. The effects of these driving factors on the population diversity and distribution of waterbird guilds were different. Finally, countermeasures and suggestions for the functional maintenance and key node restoration of waterbird habitats in Yancheng coastal wetlands were proposed.